Implementasi Finite State Automata pada Mesin Otomatis Es Krim - Alda Zevana Putri Widodo; Windu Gata; Sri Rahayu; Jordy Lasmana Putra; Laela Kurniawati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Technology is increasingly developing to help various human activities. The application of technology that has a significant influence in the industrial sector is automatic machines. An automatic machine is a technology chain whose concept is to make manual activities automatic with the aim of carrying out production and making higher quality output. This study uses two methods, namely the analytical method by obtaining information from the relevant literature to analyze previously about the automatic ice cream machine and develop from the old version. The formal method is to analyze the operation of automatic machines starting from reading input to final completion to provide results from automatic machines and designing ice cream machine applications using visual studio applications. The results of this study have passed the JFLAP application testing and can be an option to analyze the automatic ice cream maker machine by recognizing the input patterns given by the user.